Radiometric Wireless Sensor Network Monitoring of Partial Discharge Sources in Electrical Substations - Yong Zhang; David Upton; Adel Jaber; Hamd Ahmed; Bahghtar Saeed; Peter Mather; Pavlos Lazaridis; Alexandre Mopty; Christos Tachtatzis; Robert Atkinson; Martin Judd; Maria de Fatima Queiroz Vieira; et al. (International Journal of Distributed Sensor Networks)
A wireless sensor network (WSN) with the potential to monitor and locate partial discharge (PD) in high-voltage electricity substations using only received signal strength (RSS) is proposed. The advantages of an RSS-based operating principle over more traditional methods (e.g., time-of-arrival and time-difference-of-arrival) are described. Laboratory measurements of PD that emulate the operation of a PD WSN are presented. The hardware architecture of a prototype PD WSN is described and the particular challenges of an RSS-based location approach in an environment with an unknown, and spatially varying, path-loss index are discussed. It is concluded that an RSS-based PD WSN is a plausible solution for the monitoring of insulation integrity in electricity substations.